Desa Kreatif Mengolah Singkong (Manggleng) Desa Andalan Kecamatan Bayan Kabupaten Lombok Utara - Shakty, Dede Jayatama; Tamelaputri, Gina Shofyana; Maulana, Arman; Istiara; Sari, Indah; Nurhayati (Indra Institute Research & Publication, 2024)
Real work lectures (KKN) are a form of community service activities by students with a cross-scientific and sectoral approach at certain times and regions in Indonesia. Implementation of thematic KKN activities usually lasts 4 months or 6 months). In village level areas. The Directorate General of Higher Education in Indonesia has required every university to implement KKN as an extra-curricular activity that combines the tri dharma of higher education, namely: Education, research and community service. Mainstay village is one of the villages in Bayan sub-district, North Lombok district. Where mainstay villages are villages where the average population works as farmers and livestock breeders, regarding the work of residents in mainstay villages, students found a problem that became the basis for making work programs, namely the lack of knowledge of the people in mainstay villages about managing natural resources. As we know, it is important to utilize or rely on natural resources to improve the economy. Based on this situation analysis, the implementation of the thematic KKN community service program for building villages is to help the mainstay village government of Bayan sub-district, North Lombok district to provide outreach on managing natural resources such as how to process cassava into snacks or snacks.